Ex vivo effects of naphthoquinones on allergen-sensitized mononuclear cells in mice. (September 2016) - Tanaka, M; Inoue, K; Shimada, A; Takano, H
Naphthoquinone (NQ), one of the extractable chemical compounds of diesel exhaust particles, enhances allergic asthma traits in mice. However, it remains unknown whether: (1) several types of NQs have the same potential to facilitate allergies; and (2) NQs synergistically disrupt the functional phenotypes of immune cells. The aim of the present study was to investigate the effects of two types (1, 2- and 1, 4-) of NQs on sensitized mononuclear cells using an ex vivo assay. Male BALB/c mice were repeatedly and intraperitoneally administered ovalbumin (OVA: 20 µg) plus alum with or without two different doses of each NQ. After the final administration, splenocytes (mononuclear cells) were isolated from these mice and cultured in the presence of OVA. Helper T-related cytokines in the culture supernatants and downstream molecules were then evaluated. Protein levels of interferon-γ were higher in the supernatants from 1, 2-NQ and 1, 4-NQ at low dose + OVA-exposed mononuclear cells following the OVA stimulation than in those from OVA-exposed mononuclear cells. Interleukin (IL)-13 levels were higher in the supernatants from low dose NQs + OVA-exposed mononuclear cells. IL-17 levels were significantly higher in the supernatants from low dose 1, 2-NQ + OVA-exposed mononuclear cells. The quantity of phosphorylated STAT6 in the nuclei of these cells was significantly greater in the low dose NQ + OVA groups than in the OVA group. These findings suggest NQs differently enhance allergen sensitization in the context of the Th response against mononuclear cells such as lymphocytes.